2017
DOI: 10.1631/jzus.b1600139
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanism of high-mobility group nucleosomal-binding domain 2 on the Gram-negative bacteria Escherichia coli

Abstract: As an antimicrobial peptide (AMP), HMGN2 possessed a good capacity for antibacterial and antibiofilm activities on E. coli K12. This capacity might be associated with disruption of the bacterial membrane and combination of DNA, which might affect the growth and viability of E. coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…In several instances, the isolated alpha-helical domain peptide of HMGN2 has been shown to possess the same antimicrobial activity as full length HMGN2 [81]. In addition, HMGN2 seems to induce autophagy, a novel antimicrobial pathway, and protects bladder epithelial cells from infection by E. coli and other Gram-negative bacteria [82][83][84]. In agreement, recent studies indicated that deficiency in HMGN2 affected macrophage polarization and non-tuberculosis mycobacterial survival in macrophages [85].…”
Section: Immune Functionssupporting
confidence: 53%
“…In several instances, the isolated alpha-helical domain peptide of HMGN2 has been shown to possess the same antimicrobial activity as full length HMGN2 [81]. In addition, HMGN2 seems to induce autophagy, a novel antimicrobial pathway, and protects bladder epithelial cells from infection by E. coli and other Gram-negative bacteria [82][83][84]. In agreement, recent studies indicated that deficiency in HMGN2 affected macrophage polarization and non-tuberculosis mycobacterial survival in macrophages [85].…”
Section: Immune Functionssupporting
confidence: 53%
“…Yonezawa [ 53 ] reported that tachyplesin I exerts its antimicrobial activity by binding to DNA, thus inhibiting the synthesis of macromolecules. Moreover, the antimicrobial activity of HMGN2 against E. coli might be associated with its ability to bind to DNA [ 54 ]. Therefore, BCp12 can bind to DNA in vitro and affect gene transcription and translation, consistent with expression changes of cell membrane-related protein findings.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial infection is still a significant cause of human disease and even death [1] . In recent years, the rapid rise in drug resistance of pathogens, coupled with the rapid emergence of new microbial pathogens, has posed a considerable threat to human health [2–4] . How to improve antibiotic resistance has become a major problem in hospitals and community settings.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In recent years, the rapid rise in drug resistance of pathogens, coupled with the rapid emergence of new microbial pathogens, has posed a considerable threat to human health. [2][3][4] How to improve antibiotic resistance has become a major problem in hospitals and community settings. At present, there are a variety of antimicrobial drugs, but most of the pathogen resistance to these drugs is on the rise.…”
Section: Introductionmentioning
confidence: 99%